2023
DOI: 10.21203/rs.3.rs-2214350/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of the relationship between bullying and depressive symptoms in children and adolescents

Abstract: Childhood and adolescence are critical periods for physical and mental development; thus, they are high-risk periods for the occurrence of mental disorders. The purpose of this study was to systematically evaluate the association between bullying and depressive symptoms in children and adolescents. We searched the PubMed, MEDLINE and other databases to identify studies related to bullying behavior and depressive symptoms in children and adolescents. A total of 31 studies were included, with a total sample size… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Consistent with our findings, a cross-sectional study of 2,155 students found that participants who were bullied had higher levels of depression [28]. Another meta-analysis suggested that children and adolescents who experience bullying were associated with a higher incidence of depression, with an odd ratio of 2.77 [62]. A study used an SEM to explore the relationship between bullying and depressive symptoms in 4,289 Italian adolescents and found a significant positive association [63].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our findings, a cross-sectional study of 2,155 students found that participants who were bullied had higher levels of depression [28]. Another meta-analysis suggested that children and adolescents who experience bullying were associated with a higher incidence of depression, with an odd ratio of 2.77 [62]. A study used an SEM to explore the relationship between bullying and depressive symptoms in 4,289 Italian adolescents and found a significant positive association [63].…”
Section: Discussionsupporting
confidence: 89%
“…Depression is one of the most common mental health problems among children and adolescents with a risk of future, recurring episodes and disrupted transition to adulthood. A meta-analysis of 31 studies (total sample size of 133 688 individuals) showed that the risk of depression in children and adolescents who were bullied was 2.77 times greater than of those who were not bullied; the risk of depression in bullying children/adolescents was 1.73 times greater than in those who did not bully; and the risk of depression in individuals who bullied and experienced bullying was 3.19 times greater than that in nonbullying-bullied individuals [13 ▪ ].…”
Section: Impact Of Bullyingmentioning
confidence: 99%
“…Children exposed to some vulnerable conditions, including bullying victimization [7,8], self-harm behavior [9], parental divorce [2], and left-behind experience [10] ("left-behind children" refers to children whose fathers or mothers or both parents have migrated to another city outside of their original residence area for six months or more, and also means long-term parental absences [11], reflecting a phenomenon deeply rooted in China's population mobility and urbanization. ), face a higher risk of depression and suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Syndemics may heighten the vulnerability of children to depression and suicide, while risk factors associated with these mental health conditions can also foster the development of syndemic states. Childhood depression and suicide can stem from various factors [2,[7][8][9][10], including bullying, self-harm behavior, parental divorce, and left behind experiences, all of which may elevate the risk of depression and suicide. These multiple factors can interact and mutually influence each other, exacerbating children's depression and suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%